Understanding Boundary Objects Through Context-Mechanism-Outcome Configurations: A Critical Realist Study of Design-Driven Innovation Capabilities - Riarni Adina Ardanareswari; Togar Mangihut Simatupang; Mursyid Hasan Basri; Maria Widyarini (Research Synergy Foundation, 2025)
This conceptual study employs a Critical Realist approach with context-mechanism-outcome (CMO) logic to examine how boundary objects facilitate design-led innovation through dynamic capability development. It is conceptually framed by boundary object theory and dynamic capability theory. This study develops a conceptual framework linking different types of boundary objects to key dynamic capabilities (sensing, seizing, reconfiguring) and posits that these shared artefacts and processes act as generative mechanisms driving innovation outcomes across diverse contexts. This CMO-based perspective provides a nuanced explanation of how specific contexts activate these mechanisms to shape innovation results. The primary contribution of this study is a set of theoretical propositions delineating how various boundary objects serve as generative mechanisms in design-led innovation. This bridges boundary object theory with dynamic capability theory and enriches our understanding of cross-boundary knowledge integration and organizational adaptability.